Impacts of the social security programs on the employment status of informal labor in rural Vietnam - Vu, Hung Van; Ho, Huong (Journal of Social Economics Research, 2024)
The social welfare system is an important way to provide employment and income for informal labor in the context of shock economies in rural areas. This study evaluates factors impacting the employment status of rural informal labor during the time of the COVID-19 pandemic in rural Vietnam. This paper uses two models, including a binary logistic regression model and a quantile regression model, with survey data collected from 215 rural informal laborers. The results show that marital status, education, and health positively affect employment status. However, age, gender, and head of household are not identified as significant factors. The results also show that single laborers have lower chances of employment because they do not have to take care of raising their children and other members of their families. Furthermore, our models also confirm that rural informal laborers entitled to basic living allowances are less likely to be employed, but the finding is that employment and entrepreneurship services lead to a higher likelihood of being used among these laborers during COVID-19. Besides, this paper gives some policies to help informal laborers find jobs during the COVID-19 pandemic. Primarily, the research focused on the influence of social security programmes on the employment situation of rural informal labor in emerging nations such as Vietnam, particularly amid economic upheavals like the COVID-19 pandemic.